The Use of Information Technology in Academic Administration by School Administrators under the Bangkok Metropolitan Area Office of Primary Education - กาจสาลีการ, เขมิกา; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this study were to 1) examine the use of information technology in academic administration by school administrators, 2) compare the use of information technology in academic administration by school administrators categorized by gender, position, educational qualifications, work experience, and school size, and 3) investigate guidelines for developing the use of information technology in academic administration by school administrators under the Bangkok Metropolitan Area Office. The sample consisted of 285 school administrators and teachers from schools under the Bangkok Metropolitan Area Office, selected using the Krejcie and Morgan sample table. Stratified random sampling and purposive sampling were employed. The data collection instrument was a 5-level Likert scale checklist with an Index of Content Validity (IOC) of 0.50-1.00 and a reliability coefficient of .95. Statistical analyses included frequency, percentage, mean (X), standard deviation (S.D.), content validity index, and reliability coefficient. The t-test and the F-test using one-way analysis of variance (ANOVA).           The research findings revealed the following: 1. The study of the level of information technology use in academic administration by school administrators showed that overall at a high level. Ranked from highest to lowest mean scores, the areas of use were: teaching and learning management in schools, internal quality assurance and educational standards, and the development or implementation of providing feedback on the development of local curriculum content. The study of the appropriateness and usefulness of guidelines for developing the use of information technology in academic administration showed that, overall was at a high level. Ranked from highest to lowest mean scores, the areas of use were: teaching and learning management in schools, internal quality assurance and educational standards, and the development or implementation of providing feedback on the development of local curriculum content. 2. A comparison of teachers' opinions on the use of information technology in academic administration by school administrators, categorized by gender, position, educational qualifications, work experience, and school size, revealed statistically significant differences at the .05 level. A one-way analysis of variance, categorized by working experience and school size, on the use of information technology in academic administration by school administrators revealed statistically significant differences at the .05 level. 3. The guidelines for developing the use of information technology in academic administration by school administrators in all 17 areas under the Bangkok Metropolitan Area Educational Service Area Office had steps and processes that could be fully applied in all areas.